Visual distraction during word-list retrieval does not consistently disrupt memory - Rae, Pamela J. L.; Perfect, Timothy J. (Frontiers in Psychology, 2014)
Glenberg, Schroeder and Robertson (1998) reported that episodic memory is impaired by visual distraction and argued that this effect is consistent with a trade-off between internal and external attentional focus. However, their demonstration that visual distraction impairs memory for lists used 15 consecutive word lists, with analysis only of mid-list items, and has never been replicated. Experiment 1 (N=37) replicated their study, and found no overall effect of distraction on recall for the entire lists. However it did replicate the impairment for mid-list recall. Experiment 2 (N=64) explored whether this pattern arises because the mid-list items are poorly encoded (by manipulating presentation rate) or because of interference. Experiment 3 (N=36) also looked at the role of interference whilst controlling for potential item effects. Neither study replicated the pattern seen in Experiment 1, despite reliable effects of presentation rate (Experiment 2) and interference (Experiments 2 and 3). Experiment 2 found no effect of distraction for mid-list items, but distraction did increase both correct and incorrect recall of all items suggestive of a shift in willingness to report. Experiment 3 found no effects of distraction whatsoever. Thus, there is no clear evidence that distraction consistently impairs retrieval of items from lists, contrary to the embodied cognition account used to explain the original finding.